Shuttle Run Training On The Physical Performance Of Persik Kendal Football Players - Nidomuddin, Muhammad; Pramana, Aditya Ramadhan; Pamungkas, Hari; Habibi, Ahmad Ilham; Mardikaningsih, Agusti (Jurnal Pendidikan Jasmani (JPJ), 2025)
Study this aiming for know influence shuttle run training against performance physique player Persik kendal football. Shuttle run is one of the form very important agility training in sport football, because involving movement fast, change direction, and speed reaction. The research method used is method experiment with pre-test and post-test design one group. Sample in study This is 20 players active Persik Kendal who follows the training program for 6 weeks with frequency 3 times per week. Instrument measurement covering test test 30 meter sprint speed, and power hold. The results of the data analysis show that there is improvement significant in aspects agility, speed and power stand after undergo the shuttle run program. With Thus, shuttle run practice is proven give influence positive to performance physique player Kendal Peach football.